Dėl kai kurių įvardžių kilmės - Rosinas, Albertas (Baltistica, 1984)
On the origin of some pronouns This article is concerned with the origin of the Baltic general pronouns *visas, *visei, *visa “all”, the Lithuanian adjectival pronouns of (k)-oks “what” type and the Prussian stas “this”. 1. The synchronic semantic analysis of the Baltic general pronouns (Lith. vìsas, visì, vìsa, Lat. viss, visi, OPr. *wiss, wissai, wissa(n)) indicates that the meaning of the pronouns in question is in close affinity to the concept of multitude. The plural forms visi, Lat. visi, Pr. wissai and the absolute forms vìsa, Lat. viss, Pr. wissa(n) usually have the meaning of general pronouns; the singular forms, however, have the meaning of general pronouns in combination with collective nouns. When combined with other nouns, they acquire the meaning of adjectives denoting size. The above-mentioned semantic structure was inherited from the Baltic parent language. Since the Baltic general pronouns under discussion are closely related to the concept of multitude, they can be regarded as derivatives from the reduced grade vis- of the verbal stem *veis- “to increase”, “to multiply”, “to procreate”, cf. Lith. veisti(s) and visti, Lat. veist, viest (ies) and Pr. wēisin “fruit”. The interpretation presented above can be verified by looking at the origin of general pronouns in other Indo-European and non-Indo-European languages from verbs meaning “to increase”, “to grow”, “to multiply”, “to procreate”, “to cultivate, raise”, “to be”, “to exist”, “to stand” and “to live”. 2. Diachronically the Lithuanian pronouns of (k)-oks type are not exclusively derived from the suffix *-āk-; if they were derived from the suffix *-āk- only, in Modern Lithuanian there would be pronouns with o- resp. ā- stems, such as *kokas, *koka, cf. О SI. kаkъ, kaka, kako. On the basis of the forms kokìs resp. kok found in old literary texts and dialects one may conclude that the pronouns in question are compounds formed from collocations whose first component is the uninflected form *(k)-āka which, in its turn, is derived from the pronoun stems *kita-, *i-or *ši-, *ta-, *ana-, *ka-, *(v)eina- > viena- and from the comparative suffix *-āk-. The second component of the compound pronouns in question is the enclitic pronoun * (j) is (resp. * (j) ī) which, according to the law of Wackernagel, is the second member of the morphological sentence. 3. According to the synchronic semantic analysis the Prussian demonstrative pronoun stas can be considered a pronoun denoting distance and having the distinctive feature of proximity. The pronoun stas can be regarded as a compound formed from *si and *tas, or as a compound formed from the collocation *se tas, cf. Lith. dial, še tàs “this”.